Respuestas

  • Usuario de Brainly
2014-02-24T16:08:21+01:00
6√3 = √3(6^2) =√(3*36)=√108
4x²∛y² =∛[4^3(x^2)^3y^2 ] =∛(64x^6y^2)

2x/y =*(2x/y)^4 = *16x^4/y^4
√ala 4ta de 32x^3/y^3




2014-02-24T16:10:09+01:00
6√3=  \sqrt{ 6^{2} *3} = \sqrt{ (2*3)^{2} *3} =\sqrt{ 2^2*3^{2} *3} =\sqrt{ 2^2*3^{3}}

4x²∛y²  =   \sqrt{ (4x^{2})^3y^2}=\sqrt{ (2^2*x^{2})^3y^2}=\sqrt{ (2^2)^3(x^{2})^3y^2}=\sqrt{ 2^6*x^{6}y^2}

2 \frac{x}{y} \sqrt[4]{ \frac{y}{x} } = \sqrt[4]{(2 \frac{x}{y})^4\frac{y}{x} } =\sqrt[4]{\frac{2^4x^4y}{y^4x} } =\sqrt[4]{\frac{2^4x^3}{y^3} }

Espero te sea de utilidad, No olvides xfav calificar nuestras respuestas. Exito